1994
DOI: 10.1007/bf03348962
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term simvastatin treatment on testicular and adrenal steroidogenesis in hypercholesterolemic patients

Abstract: Simvastatin is an inhibitor of 3-hydroxy-3-methyl glutaryl coenzyme A (HMG-CoA) reductase, the key enzyme in the synthesis of cholesterol, recently introduced in the therapy of hypercholesterolemic patients. Cholesterol is the precursor of the biosynthesis of steroid hormones; thus, a reduction of the availability of cholesterol in the adrenal and testicular cells may reduce the synthesis of corticosteroids and androgens. To establish whether chronic therapy with simvastatin interferes with the integrity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Effect of high dose atorvastatin on gonadal steroidogenesis was similar to effect of regular doses. Our results are consistent with prior research on this subject, most of which found no effect of statin treatment on male gonadal function ( Travia et al, 1995 ), ( Dobs et al, 1993 ), ( Azzarito et al, 1992 ), ( Bernini et al, 1994 ), ( Jay et al, 1991 ), ( Purvis et al, 1992 ) however in these prior studies mean post treatment LDL levels are consistently above 100 mg / dl, reaching around 180 mg / dl in one of them. ( Travia et al, 1995 ) These post treatment LDL levels are considered unacceptable in current medical practice, particularly in very high risk patients requiring secondary prevention for coronary heart disease.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Effect of high dose atorvastatin on gonadal steroidogenesis was similar to effect of regular doses. Our results are consistent with prior research on this subject, most of which found no effect of statin treatment on male gonadal function ( Travia et al, 1995 ), ( Dobs et al, 1993 ), ( Azzarito et al, 1992 ), ( Bernini et al, 1994 ), ( Jay et al, 1991 ), ( Purvis et al, 1992 ) however in these prior studies mean post treatment LDL levels are consistently above 100 mg / dl, reaching around 180 mg / dl in one of them. ( Travia et al, 1995 ) These post treatment LDL levels are considered unacceptable in current medical practice, particularly in very high risk patients requiring secondary prevention for coronary heart disease.…”
Section: Discussionsupporting
confidence: 92%
“…( ATP III fi nal report, 2002 ) So, it may be controversial to consider the data generated by prior studies on this issue as valid in contemporary clinical practice. The main reason for this confounding factor is that the effect of peripheral LDL on steroidogenesis is dose dependent ( Tureck and Strauss, 1982 ) and post treatment LDL levels of prior studies on this issue are quite higher ( Travia et al, 1995 ), ( Dobs et al, 1993 ), ( Azzarito et al, 1992 ), ( Bernini et al, 1994 ), ( Jay et al, 1991 ), ( Purvis et al, 1992 ) than the contemporary guideline recommendations. Another hypothetical factor that may alter effect of different statins on steroidogenesis is the hydrophilic or lipophillic property of the individual statin molecule.…”
Section: Discussionmentioning
confidence: 97%
“…Some studies have suggested that statins reduce serum testosterone levels 4648 , but these reductions were small or caused by statin doses that were higher than commonly used in clinical practice. Other observational studies 49,50 and two clinical trials 51,52 found no association between statin use and serum androgen levels. A study in 1,812 men in the Boston Area Community Health Survey cohort of which 237 men were statin users found no association between statin use and serum androgen levels 53 .…”
Section: Mechanisms Of Prostate Cancer Preventionmentioning
confidence: 94%
“…The four existing studies on simvastatin (Purvis et al 1992;Balestrieri et al 1990;Bernini, Argenio, Gasperi, Vivaldi, Franchi and Salvetti 1994; Rossato, Guarneri, Lavagnini, Padovan and Foresta 1993), did not demonstrate any reduction of testo sterone after 3.5, 6 and 12 months of treatment. However, the fourth (Rossato et at.…”
Section: Discussionmentioning
confidence: 92%